NUANCE IN SIMPLE AND PAST TENSE PATTERNS BY INDONESIAN EFL LEARNERS: A CONTRASTIVE ANALYSIS - Lalu Suhirman (Center of Language and Cultural Studies [CLCS], 2016)
This article aims to identify the differences between Indonesian and English in constructing affirmative, negative, and interrogative sentences in simple present and present progressive, and simple past and past progressive tenses. This research is descriptive qualitative design. The 40 first semester students of STIKOM Jayapura was selected as research subject. The result indicated that Contrastive Analysis was the systematic study of a pair of languages with a view to identifying their differences and similarities with the assumption the different elements between the native (Indonesian) and the target (English) language caused learning problems, while similar elements did not cause any problems. Contrastive analysis hypothesis is criticized for not all problems predicted by contrastive analysis always appear to be difficult for the students. Errors that do turn up are not predicted by contrastive analysis, but if errors cannot be identified through Contrastive Analysis, it will be suggested using Error Analysis.